Analisis perawatan mesin tenun 0208 pada kain 11717 menggunakan metode Overall Equipment Effectivenes (OEE) dan Six Big Losses pada PT. Libolon Fiber System - Wibowo, Priyo Ari; Nugraha, Imam Wahyu (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Libolon Fiber System is a company that produces woven fabrics. To optimize the quality and quantity of production, the company must carry out maintenance actions on the machine. The research carried out focused on the 0208 weaving machine which is in the weaving department. Problems that occurred at PT. The Libolon Fiber System is that the production target was not achieved due to a decrease in efficiency, one of the causes of the decrease in efficiency was because there were many sudden machine breakdowns while the production process was in progress. Based on these constraints, an analysis was carried out implementing the overall equipment effectiveness and six big losses method. The results of the analysis show that the overall equipment effectiveness (OEE) on the 0208 weaving machine is obtained on average at 79.50%, where the factors that influence OEE in the six big losses are idling and minor stoppage losses with an average of 23%.